Sublethal effects of sulfoxaflor on the development and reproduction of the brown planthopper, Nilaparvata lugens (Stål). (April 2019) - Liao, Xun; Ali, Ehsan; Li, Wenhao; He, Biyan; Gong, Peipan; Xu, Pengfei; Li, Jianhong; Wan, Hu
Abstract: In the present investigation, the sublethal effects of sulfoxaflor on the brown planthopper (BPH), Nilaparvata lugens, an important rice pest in Asia, were evaluated via the age-stage, two-sex life table procedure. Our results demonstrated that the adult longevity and fecundity values of F0 individuals were significantly lower in the LC30 group than in the control group. Compared with those of the control group, the preadult period; female adult period; total preoviposition period (TPOP); longevity; fecundity; hatchability; and development time of 1st, 3rd, and 4th instar nymphs of the F1 individuals of the LC30 group were significantly reduced, whereas no significant differences were found between the LC15 group and the control group. The development time of 5th instar nymphs was significantly shorter in both the LC15 and LC30 groups than in the control group. However, the development time of 2nd instar nymphs and the adult preoviposition period (APOP) were significantly longer in the LC15 group than in the control group. In addition, the net reproductive rate ( R 0 ), mean generation time ( T ) and gross reproduction rate ( GRR ) were significantly lower in the LC30 group than in the control group. However, the intrinsic rate of increase ( r i ) and finite rate of increase ( λ ) values were not influenced by low lethal concentrations of sulfoxaflor. These results indicated that the sublethal effects of sulfoxaflor reduce the survival and reproductive capability of N. lugens in successive generations. Our findings would be useful for assessing the overall effects of sulfoxaflor on N. lugens . Graphical abstract: Image 1 Highlights: Sublethal effects of sulfoxaflor reduce adult longevity, fecundity and hatchability of N. lugens. Sublethal effects of sulfoxaflor increase the development ratio of nymph stages of N. lugens. Sublethal effects of sulfoxaflor adversely affects the long-term life table parameters of N. lugens.